2020
DOI: 10.1371/journal.pone.0232598
|View full text |Cite|
|
Sign up to set email alerts
|

Vulnerability profiles and prevalence of HIV and other sexually transmitted infections among adolescent girls and young women in Ethiopia: A latent class analysis

Abstract: Background Adolescent girls and young women (AGYW) aged 15-24 years have among the highest risk for HIV and other sexually transmitted infections (STI) across sub-Saharan Africa. A latent class analysis (LCA) was conducted to identify intersecting social-and structural-level determinants of HIV/STI acquisition among AGYW in Ethiopia. Methods AGYW were recruited from venues using time-location sampling, completing an interviewer-administered behavioral survey and biological testing for HIV, syphilis, and chlamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
(69 reference statements)
2
26
0
4
Order By: Relevance
“…High rates of STIs among young people reveal the high levels of unprotected sex, which puts them at risk for contracting HIV. STIs are most frequent in young people aged 15-24, and 50 per cent of all HIV infections are among young people, most of whom contract HIV before they are 20 years old [9] .…”
Section: Resultsmentioning
confidence: 99%
“…High rates of STIs among young people reveal the high levels of unprotected sex, which puts them at risk for contracting HIV. STIs are most frequent in young people aged 15-24, and 50 per cent of all HIV infections are among young people, most of whom contract HIV before they are 20 years old [9] .…”
Section: Resultsmentioning
confidence: 99%
“…Em estudos feitos a fim de verificar a incidência dessas infecções em mulheres jovens e adolescentes em países em desenvolvimento na África, tais quais apresentam os fatores associados mais aflorados, mostram que em grupos que se caracterizavam por algumas dessas características: baixa escolaridade, histórico de migração, orfandade, desemprego, insegurança alimentar, podem representar até o dobro de casos em relação aos outros grupos. (Comins et al 2020) Silva et al (2015) realizaram estudo sobre como os enfermeiros percebem as vulnerabilidades para as DST/Aids no contexto da adolescência, e identificaram que a adolescência é fenômeno multidimensional, envolvendo aspectos relacionados aos sentimentos de invulnerabilidades para as práticas sexuais, as iniquidades de gênero, a quais a mulher encontra-se em processo de desigualdade, lacunas do conhecimento, ou seja, a falta de informação sobre os riscos de infecção e quanto as formas de prevenção. Neste contexto, o enfermeiro por atuar nos diversos níveis de atenção à saúde, deve ter uma percepção e atuação fundamentada nos temas transversais as questões de saúde, como gênero, sexualidade, IST/HIV/Aids, dentre outros que possam contribuir para redução das vulnerabilidades.…”
Section: Resultsunclassified
“…Ademais, aprofundando o tema sobre as condições de vulnerabilidades desses países, no ano de 2017 a região subsaariana representou dois terços das infecções por HIV no mundo, Research, Society and Development, v. 10, n. 1, e59910111867, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i1.11867 sendo meninas adolescentes de 15 a 24 anos sendo até três vezes mais o alvo em comparação aos meninos da mesma categoria. (Comins et al 2020) Outro fator a considerar é o fato da coinfecção, haja vista que é uma possibilidade bastante eminente para esse tipo de infecção. Estudos mostram que pessoas que possuem múltiplos parceiros tem um risco aumentado de coinfecção para HIV.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…have found that the above mentioned factors, including economic vulnerability, reduce the likelihood of condom use among women sex workers. 4-8 Low levels of social support have a significant effect on high-risk sexual behavior and sexually transmitted infections among women (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%